Effect of the maximum thickness of a composite airfoil on the performance of a helical axial-flow gas-liquid multiphase pump - Han, Wei; Nan, Haozhi; Ju, Pengpeng; Zhang, Huan; Li, Fengqing; Li, Rennian (Frontiers in Energy Research, 2022)
Operating efficiency and reliability are major problems that restrict gas-liquid multiphase pumps, which are core pieces of equipment used in deep-sea oil and gas exploration and transportation. In this paper, a 100-20x helical axial-flow gas-liquid pump is taken as the research object. The Euler multiphase flow model and SST k-ω turbulent model are used to model the multiphase pump. By exploring the airfoil composite position and the maximum thickness composite scheme, a mathematical model for the head coefficient and efficiency of the multiphase pump with respect to the relative thickness is established, and the external and internal flow characteristics of the modified multiphase pump are analyzed. We explore the influence of the composite position and the maximum thickness variation law of the composite airfoil on the performance of the mixed pump and determine the final airfoil composite scheme. We found that a change in the maximum thickness of the composite airfoil gives the external curve of the multiphase pump a "hump"-like characteristic, which shows that the head coefficient and efficiency increase first and then decrease with the increase in the maximum thickness of the composite airfoil. When the composite position is in the middle of the airfoil, the airfoil maximum thickness is 1.25mm and the gas-phase volume fraction is 70%. Moreover, the head coefficient and efficiency of the multiphase pump reach their maximum values; the head coefficient and efficiency increase by 2.4% and 1.16%, respectively, compared with the basic model.